2016
DOI: 10.1108/bpmj-10-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of preferred customer enablers from supplier’s perspective

Abstract: Purpose The purpose of this paper is to identify, rank, classify and establish the structural relationships between the preferred customer enablers (PCEs). This analysis would assist a manufacturer in selectively exercising the PCEs and effectively run-through the concept of reverse marketing in the buyer-supplier relationships. Design/methodology/approach In the current study, the interpretive structure modelling and Fuzzy Matriced’ Impacts Croisés Appliquée á un Classement methods are used to analyze and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Research to date has identified several tangible benefits associated to the preferred customer status, such as: early access to supplier innovation and support in the research and development programs (Schiele, 2012;Kumar and Routroy, 2016b;Patrucco et al, 2020); better quality products (Nollet et al, 2012); improved availability of products, services and resources (Steinle and Schiele, 2008;Nollet et al, 2012); price benefits (Schiele et al, 2011;Nollet et al, 2012); prioritized services (Hüttinger et al, 2012); faster transactions and on time deliveries (Nollet et al, 2012); reduced risk despite the increasing dependency (Schiele and Vos, 2015;Reichenbachs et al, 2017); lower transaction costs and better economies of scale (Bew, 2007;Bemelmans et al, 2015;Vos et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research to date has identified several tangible benefits associated to the preferred customer status, such as: early access to supplier innovation and support in the research and development programs (Schiele, 2012;Kumar and Routroy, 2016b;Patrucco et al, 2020); better quality products (Nollet et al, 2012); improved availability of products, services and resources (Steinle and Schiele, 2008;Nollet et al, 2012); price benefits (Schiele et al, 2011;Nollet et al, 2012); prioritized services (Hüttinger et al, 2012); faster transactions and on time deliveries (Nollet et al, 2012); reduced risk despite the increasing dependency (Schiele and Vos, 2015;Reichenbachs et al, 2017); lower transaction costs and better economies of scale (Bew, 2007;Bemelmans et al, 2015;Vos et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the purchasing department should carefully segment suppliers, identifying those who are really strategic. This would allow the organization to better adapt its approaches and practices according to those of the most important suppliers (Schiele, 2012;Kumar and Routroy, 2016a). In fact, the purchasing department could take a leadership position to effectively coordinate activities across several organizational members and the supplier, and avoid some pitfalls in the preferred customer relationship.…”
Section: Literature Reviewmentioning
confidence: 99%